The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1046/j.1464-410x.2000.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between early biochemical failure and perineural invasion in pathological T2 prostate cancer

Abstract: Of those with PSA recurrence, 14 had PNI, one had no PNI and in two there was no comment on PNI.In comparison, only 10 of the 17 patients with recurrence had a Gleason sum of o7. Conclusion Perineural invasion seems to be an important predictor of early outcome in patients with organcon®ned prostate cancer treated by prostatectomy. In this series it was the most sensitive predictor of biochemical failure. A more detailed pathological evaluation of prostate cancer may allow the clinician to provide closer surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 11 publications
3
24
1
1
Order By: Relevance
“…16 The presence of perineural invasion has also been shown to have a greater positive-predictive value for PSA recurrence than either Gleason score Z7 and preoperative serum PSA 410 ng/ml. 22 These findings, however, are contradicted by the rather surprising observation that the presence of perineural invasion was associated with increased biochemical recurrence-free survival interval. 19 While perineural invasion is recognized as a common feature of prostate adenocarcinoma in glands removed by radical prostatectomy, the proportion of involved nerves varies from series to series.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…16 The presence of perineural invasion has also been shown to have a greater positive-predictive value for PSA recurrence than either Gleason score Z7 and preoperative serum PSA 410 ng/ml. 22 These findings, however, are contradicted by the rather surprising observation that the presence of perineural invasion was associated with increased biochemical recurrence-free survival interval. 19 While perineural invasion is recognized as a common feature of prostate adenocarcinoma in glands removed by radical prostatectomy, the proportion of involved nerves varies from series to series.…”
Section: Discussionmentioning
confidence: 97%
“…19 While perineural invasion is recognized as a common feature of prostate adenocarcinoma in glands removed by radical prostatectomy, the proportion of involved nerves varies from series to series. In studies based upon a review of pathology reports, without re-examination of histology, perineural invasion was noted in 31.9-60.5% of specimens, 16,22,23 while in series in which review of sections was undertaken, the incidence ranged from 74 to 84%, with the majority series being in the order of 75%. [13][14][15][17][18][19] Our finding that 90% of specimens showed perineural invasion, following identification of nerves using S-100 protein immunostaining, demonstrates that even after review, some nerves showing perineural invasion are overlooked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of studies have found that PNI predicts BCR on univariable analysis, [7][8][9][10][11][12][13][14][15] only two studies have reported PNI as a significant predictor on multivariable analysis. 8,13 Both of these studies examined relatively small cohorts of fewer than 250 participants.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies that report on it, it is an observational finding. For example, in one study (89), of the 17 patients that recurred, 1 4 ( 8 2 % ) h a d p e r i n e u r a l i n v a s i o n . O t h e r t h a n t h a t observation, no real correlation of PNI with failure was possible.…”
Section: Modifying Factorsmentioning
confidence: 99%